The development of legal thought from the rule to the principle and its role in bringing popular satisfaction - Tahsin HamaSaeed Shamsaldin (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
This research in the philosophy of law field. It claims that legal thought in modern times has gone through three stages. It is assumed that the law in the beginning is only a judgment. And then turned to the legal rules, And It considered legal principles in the third phase, which means in the first stage that the ruling issued by the governor of the district (political power) is counted only law. In the second phase, the law was seen as a legal rule. Since the rule of law is separate from those who issued it and that the application of the law can imagine what is required of it and its prediction. In the third stage, the philosophers of the law went on to say that the law is a legal principle. This means that the law is transformed from an external issue into an internal matter, which is applied by the legal person in his faith and not only out of fear of the punishment imposed on him. The philosopher of the English law (Austin) is the founder of the first stage, since he shortens the law in the rules of the living ruler, while the philosopher of the famous law (Hart) represents the second stage and he wanted - as the law legal rules - complete the shortcomings in the thinking of the first stage. While the American philosopher Dworkin) brought the third phase of the legal thought (the principle stage). On the other hand, political philosophy has fundamentally changed the question of democracy and social contract. This is due to the work of the philosophers such as John Rawls and Yurgen Habermas. Today, the elected authority is no longer able to make a decision. The social contract is no longer held because of the defense of the rights of the individual, but also for the rights of the group. This indicates that the philosophy of politics has tended to focus on an internal matter which is to bring the satisfaction of the people, by which both legal and political thought have reached a common point.